EVALUASI PELAKSANAAN RENCANA PEMBANGUNAN JANGKA MENENGAH DAERAH (RPJMD) KABUPATEN BERAU TAHUN 2010-2015 BIDANG PENDIDIKAN DAN BIDANG KESEHATAN - Muhammad Wahyuddin (Jurnal Paradigma (JP), 2017)
This research was aims to analyze and describe Evaluation of Implementation the Medium Term Development Plan (RPJMD) of Berau Regency Year 2010-2015 of Education and Health. The focus of the research are: medium-term development plan in the field of Education and the medium-term development plan in the field of health. The research data obtained through interview, observation and documentation. The  results of this study illustrate the implementation of educational programs in accordance with what is stated in the document RPJMD Berau District on 4 programs implemented according to priority.